IMF Staff papers : Volume 27 No. 4. (IMF Staff Papers; IMF Staff Papers, 1980)
This paper explores components of saving and investment in an income determination framework. The current account balance known as net foreign investment in the national income and product accounts of the United States is largely determined by domestic factors that have changed the supply of national saving relative to the demand for domestic investment. Thus, the estimated rate of net foreign investment declined by almost half as much as the cyclically adjusted net national saving rate on average over the past two decades and this proportion has been growing. Cyclical variables that appear in these equations and allow them to be solved at equilibrium are themselves endogenous. The evidence suggests that measures to raise the national saving rate would contribute as much to the external adjustment of the United States as to its domestic capital stock and thence to its potential gross domestic product. Thus, the openness of the US economy cannot safely be ignored in policy discussions of saving and investment in the United States.